Fitossociologia de espécies nativas de mata ciliar no entorno do reservatório divisa, São Francisco de Paula, RS - Rorato, Daniele Guarienti (2012)
The work aims to characterize the forest structure and species composition in the area, identify the formation of clusters in the tree component and to determine the influence of soil variables in species and in groups. The study area is located at Divisa Reservoir, São Francisco de Paula, RS. The survey of the trees and shrubs vegetation was conducted in four fragments: F1 (9 ha), F2 (9 ha), F4 (2 ha) and F5 (9 ha). In each plot was performed the identification and measurement of the circumference at breast height (CAP) as the following size classes: Class I (10 x 20 m) individuals with CAP ≥ 30 cm; Class II (10 x 10 m) individuals with 15 ≤ CAP < 30 cm; Class III (5 x 5 m) individuals with 3 ≤ CAP < 15 cm and Class IV (2 x 2 m) the individuals with < 3 cm and CAP < 3 cm. The vertical structure was evaluated by the classification of the individuals surveyed on sociological classes, belonging to the sociological position 1 (PS1) individuals in the upper stratum, sociological position 2 (PS2) the stratum medium and sociological position 3 (PS3) in the lower stratum. The forest inventory data constituted a matrix parcel x species, which was used in multivariate analysis, by the method TWINSPAN, allowing the classification groups of parcels, based on the density of individuals. In addition to the vegetation, the environmental variables were obtained. The correlation between vegetation data and environmental data was performed by means of Canonical Correspondence Analysis, using the program PC-ORDTM for Windows version 5.10. The results demonstrate the formation of three distinct groups. Group 1 (GR1) represents the specific situation of riparian vegetation, Group 2 (GR2) represents a remnant of Araucaria Forest, under the influence of intensive livestock farming in the fields, and Group 3 (GR3) demonstrates an atypical situation, with the presence of species strongly influenced by the depth of the soil, and water saturation in the longest period of time. In GR1, the mixture of species of different ecological groups, with predominance of pioneer and secondary species, shows that the forest is presented in the dynamic process of succession. The GR2 has a negative influence of cattle on their structure and composition. Stand out in the riparian (GR1) Eugenia uruguayensis and Sebastiania commersoniana and clumps (GR2), the predominance are Araucaria angustifolia, Podocarpus lambertii and Myrceugenia cucullata, as main responsible for the existing formations. Furthermore, the slow decomposition of organic matter enhanced by higher humidity change the availability of nutrients for the species in place. In the woods, the constant presence of cattle negatively changes the structure of the understory, thus influencing the soil chemical characteristics. Species such as Araucaria angustifolia, Eugenia uruguayensis, Blepharocalyx salicifolius, Calyptranthes concinna, Lithraea brasiliensis, Myrsine coriacea, Ocotea pulchella e Sebastiania commersoniana can be used in the recovery and enrichment of riparian vegetation.